The Hegemony of English in Public Discourse - Exsuperantia Yohanita Irene (Lingua Cultura, 2013)
This article looks at the relation of the global role of English to the English hegemony found in the Jakarta Post articles. It highlights the readers’ point of view, specifically the arguments they used in opposing the Education and Culture Ministry plan to scrap English from Elementary School Curriculum. It underlines the contemporary phenomenon of English as a world language and the role it plays in contributing to the dominance of English reflected on the readers’ opinion.